Impact of transrectal prostate needle biopsy on erectile function: Results of power Doppler ultrasonography of the prostate. Issue 4 (7th January 2014) - Tuncel, Altug; Toprak, Ugur; Balci, Melih; Koseoglu, Ersin; Aksoy, Yagiz; Karademir, Alp; Atan, Ali
Abstract: We evaluated the impact of transrectal prostate needle biopsy (TPNB) on erectile function and on the prostate and bilateral neurovascular bundles using power Doppler ultrasonography imaging of the prostate. The study consisted of 42 patients who had undergone TPNB. Erectile function was evaluated prior to the biopsy, and in the 3rd month after the biopsy using the first five‐item version of the International Index of Erectile Function (IIEF‐5). Prior to and 3 months after the biopsy, the resistivity index of the prostate parenchyma and both neurovascular bundles was measured. The mean age of the men was 64.2 (47–78) years. Prior to TPNB, 10 (23.8%) patients did not have erectile dysfunction (ED) and 32 (76.2%) patients had ED. The mean IIEF‐5 score was 20.8 (range: 2–25) prior to the biopsies, and the mean IIEF‐5 score was 17.4 (range: 5–25; p < 0.001) after 3 months. For patients who were previously potent in the pre‐biopsy period, the ED rate was 40% ( n = 4/10) at the 3rd month evaluation. In these patients, all the resistivity index values were significantly decreased. Our results showed that TPNB may lead to an increased risk of ED. The presence of ED in men after TPNB might have an organic basis.